2022
DOI: 10.3390/brainsci12101389
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Huntington’s Disease: An Emphasis on Molecular Pathways and Prevention by Natural Remedies

Abstract: Background: Huntington’s disease is an inherited autosomal dominant trait neuro-degenerative disorder caused by changes (mutations) of a gene called huntingtin (htt) that is located on the short arm (p) of chromosome 4, CAG expansion mutation. It is characterized by unusual movements, cognitive and psychiatric disorders. Objective: This review was undertaken to apprehend biological pathways of Huntington’s disease (HD) pathogenesis and its management by nature-derived products. Natural products can be lucrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 220 publications
(229 reference statements)
0
4
0
Order By: Relevance
“…The trinucleotide (cytosine–adenine–guanine, CAG) repeat in the Huntington (HTT) gene is expressed in the brain and an expanded CAG repeat length is the main cause of HD. In addition, other genetic factors such asoxidative stress, DNA damage, mitochondrial dysfunction, neuroglia dysfunction, and protein aggregation lead to HD [ 146 , 147 ]. Recent studies have suggested that HD may be associated with gut dysbiosis, which is caused by GIT dysfunction in an HD mouse model.…”
Section: Neurological Disorders and Gbamentioning
confidence: 99%
“…The trinucleotide (cytosine–adenine–guanine, CAG) repeat in the Huntington (HTT) gene is expressed in the brain and an expanded CAG repeat length is the main cause of HD. In addition, other genetic factors such asoxidative stress, DNA damage, mitochondrial dysfunction, neuroglia dysfunction, and protein aggregation lead to HD [ 146 , 147 ]. Recent studies have suggested that HD may be associated with gut dysbiosis, which is caused by GIT dysfunction in an HD mouse model.…”
Section: Neurological Disorders and Gbamentioning
confidence: 99%
“…The most frequently, as shown by recent studies, transcriptional impairment affects neurotransmitter receptors, ion channels, and BDNF [11,12]. Aberrant huntingtin interacts with different transcription-regulating proteins (p53, CREB, CBP, and MSK-1, which control cell proliferation and DNA damage repair), PGC-1α, organelle and vesicle transporters, and dopamine 2 receptor-interacting proteins [13].…”
Section: Transcription Dysfunctionmentioning
confidence: 99%
“…Mitochondria are a link between several pathological processes: disturbances of the electron transport chain, of metabolic processes, and of calcium homeostasis [11,12].…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Huntington's disease (HD) is a progressive, dominantly inherited neurodegenerative disorder which is estimated to affect approximately one in every 10,000 people, with nearly 30,000 patients in the United States [1]. It is caused by the expansion of polyglutamine repeat (polyQ), encoded by the codon CAG, within the huntingtin (HTT) gene.…”
Section: Introductionmentioning
confidence: 99%
“…The use of protein overexpression has been widely used to examine transport [35][36][37]; however, these systems produce unavoidable artifacts that corrupt the endogenous nature of the neurite. The microfluidic chamber offers multiple advantages over other systems, the most important of which are: (1) ability to fluidically isolate distal dendrites from cell bodies; and (2) ability when coupled with exogenously applied ligands to allow for the observation of single-molecule transport in a physiologically relevant receptor/ligand setting. The separation of dendrites from neuronal soma using microfluidic devices has proven challenging but has been met with some success [38][39][40].…”
Section: Introductionmentioning
confidence: 99%